2021
DOI: 10.1155/2021/6633690
|View full text |Cite
|
Sign up to set email alerts
|

Pyrocarbon Humeral Head in a Shoulder Hemiarthroplasty: Preliminary Results at 3 Years Follow-Up and Review of the Current Literature

Abstract: Shoulder hemiarthroplasty is a viable option in young patients with an intact rotator cuff in order to preserve the native glenoid. To avoid the dreaded and expected wear of the glenoid in very active shoulders, implants with humeral head coated with a high resistant and elastic material—pyrolytic carbon—are now an option. The authors present the first pyrocarbon coated hemishoulder arthroplasty performed at our Orthopedic Department in a patient with osteonecrosis of the humeral head. At three years of follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…Different types of pyrocarbon implants exist, especially in the shoulder; and several clinical reports describe their use for treatment of challenging shoulder pathologies in young patients ( Figs. 2 and 3 ) [ 17 , 18 ].…”
Section: Pyrocarbon History and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of pyrocarbon implants exist, especially in the shoulder; and several clinical reports describe their use for treatment of challenging shoulder pathologies in young patients ( Figs. 2 and 3 ) [ 17 , 18 ].…”
Section: Pyrocarbon History and Compositionmentioning
confidence: 99%
“…In order to solve this challenge, pyrolytic carbon (pyrocarbon) in the form of pyrocarbon-coated implants or interpositional prosthetic components was introduced as an alternative weight-bearing surface that can decrease glenoid erosion in hemiarthroplasty procedures [16][17][18]. Early in vitro studies showed promising results, with reduced wear rates compared to other materials [19][20][21].…”
Section: Introductionmentioning
confidence: 99%